Staff and Students Views on Industry-University Collaboration in Engineering - Chandraseakaran, Sivachandran; Littlefair, Guy; Stojcevski, Alex (International Journal of Advanced Corporate Learning (iJAC), 2015)
The university-learning environment in engineering is not sufficient for students to become engineers. The practical role of engineering is working on real world problems in an industry environment. Industry-university collaboration seems to be actively increasing in the development of engineering education in various parts of the globe. The close relationship between industry and university is a vital component of engineering pedagogy in Australia. This research paper is focuses on analyzing staff and students views on industry-university collaboration in engineering. The staff and students are playing vital role in industry-university collaboration. It is always worth analyzing staff and students’ views about their experience on industry-university collaboration. This research inclined to conduct a paper based survey with a cohort of students in second year undergraduate engineering course and also conduct face-to-face interview with staff members in the School of Engineering at Deakin University.